Creative activities as intervention – Exploring occupational therapists’ narrative reasoning - Bodil Winther Hansen; Helle Andrea Pedersen; Lene Lauge Berring; Staffan Josephsson (Scandinavian Journal of Occupational Therapy)
Background Creative activities as intervention (CaI) in mental health promotes recovery and is an important part of occupational therapy practice. Yet few studies have explored occupational therapists’ reasoning about using CaI to trace tacit knowledge.Aims/Objectives The aim of this study was to explore occupational therapists’ reasoning on rationale and motives in co-creating a model (the CreActivity model) for CaI as a resource in mental health rehabilitation.Material and methods Co-operative inquiry and narrative theory provided the methodology for exploring eight occupational therapists’ narrative reasoning in the process of co-creating a model. Data were generated via ethnographic methods from seven co-operative inquiry group meetings and analysed through narrative analysis.Results The occupational therapists’ reasoning in using creative activities comprised building relationships and opportunity for activity. Motivating and engagement by finding ‘cracks’ and stories bridging action with the past and future using creative activities were used to create reflection, development, and empowerment.Conclusions and significance Identifying the narrative layers of occupational therapists’ reasoning on achieving core dimensions of occupational therapy may enable and support occupational therapists in the use of creative activities as intervention.